PENGARUH JENIS PUPUK ORGANIK TERHADAP PRODUKSI (BERAT UMBI) UBI JALAR (IPOMEA BATATAS L) CLON MADU (THE INFLUENCE OF TYPE OF ORGANIC FERTILIZERS AT CLON MADU SWEET POTATOES (IPOMEA BATATAS L) PRODUCTION (CORM'S WEIGHT)) - Suharno, Suharno (Jurnal Ilmu-Ilmu Pertanian, 2007)
The research of the influence of kind of organic fertilizer in clon madu sweet potato ( Ipomea batatas L) production is done in STPP trial garden (STPP, Majors of Counseling of Agriculture Yogyakarta) at October 2006 until May 2007. The goal of this research is to know the influence of various organic fertilizer at sweet potato production There are 6 treatments, control (P1), and 5 types of organic fertilizer that used are cage fertilizer (P2), paddy chaff fertilizer ( P3), wood fertilizer (P4), paddy hay fertilizer (P5), leaves fertilizer (P6). The method of this research by using one factor complete group random device, each repeated 4 times. Perception is done to mean parameter, sontrot's quantity, corm's quantity, corm's diameter, and producing of corm (corm's weight). The conclusion of this research that the treatment of some organic fertilizers have an effect on and reality different at the production of sweet potatoes, an addition paddy hay fertilizer shows that the production of sweet potatoes (corm's weight) is the highest than other fertilizer types